2x-3=33-x
7-2x=4+x
5t-6=3-4t
9-3x=-5x+4
7x+10=6x-5
Soluções para a tarefa
Respondido por
1
2x - 3 = 33 - x
3x = 36
x = 12
7 - 2x = 4 + x
- 3x = -3
x = 1
5t - 6 = 3 - 4t
9t = 9
t = 1
9 - 3x = - 5x + 4
2x = -5
x = -5/2
7x + 10 = 6x - 5
x = -15
3x = 36
x = 12
7 - 2x = 4 + x
- 3x = -3
x = 1
5t - 6 = 3 - 4t
9t = 9
t = 1
9 - 3x = - 5x + 4
2x = -5
x = -5/2
7x + 10 = 6x - 5
x = -15
Perguntas interessantes
Geografia,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás